Developing Cooperative Learning Based E-Module to Teach Basic English Grammar of the First Semester of English Study Program Students at FKIP – UIR - Ahmad, Arimuliani (J-SHMIC : Journal of English for Academic, 2017)
Achieving learning outcome requires a set of the material that can be understood easily by the students. The material should be appropriate in the learning process. It should give the opportunity for the students to learn both in the classroom and out of the classroom. The students can learn independently by using the appropriate material. However, the material of Basic English Grammar is still quite enough to give a chance for the students to practice and learn cooperatively. This research is aimed obtain e-module of Basic English Grammar, so that it can be used as a source of learning for first semester students of English Study Program of FKIP-UIR. The research method used in this study is R & D (Research and development) of Borg and Gall. The participant of this research is 30 students from first semester who learn Basic English Grammar. In this research, the researcher tried to find out students’ need because it is the first step to do in this research design. So, the data was obtained by writing test.The findings suggest that the participants made 386 errors in writing their paragraph. There are 45 errors (11.66%) of the agreement of singular and plural, 106 errors (27.46%) of the using of verb tense, 51 errors (13.21%) of the finite verb, 25 errors (2.48%) of the non-finite verb, 28 errors (7.25%) of the pronoun, 20 errors (5.18%) in using the preposition, 9 errors (2.33%) of the context of usage, 55 errors (14.25%) of the context of meaning, 22 errors (5.70%) of the word choice and 25 errors (6.48%) of word order. To sum up, the most frequent grammatical errors made by the students are errors in writing verb tense. Based on this finding, the researcher will design e-module of Basic English Grammar.